If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -63 = -10x + 145 Reorder the terms: -63 + 3x = -10x + 145 Reorder the terms: -63 + 3x = 145 + -10x Solving -63 + 3x = 145 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -63 + 3x + 10x = 145 + -10x + 10x Combine like terms: 3x + 10x = 13x -63 + 13x = 145 + -10x + 10x Combine like terms: -10x + 10x = 0 -63 + 13x = 145 + 0 -63 + 13x = 145 Add '63' to each side of the equation. -63 + 63 + 13x = 145 + 63 Combine like terms: -63 + 63 = 0 0 + 13x = 145 + 63 13x = 145 + 63 Combine like terms: 145 + 63 = 208 13x = 208 Divide each side by '13'. x = 16 Simplifying x = 16
| -2w(w+8)= | | 4x-94=98-12x | | (b+8)*(b-2)= | | x^4+4x^3-12x^2-24x-9=0 | | y=-3(19)+135 | | 12xh=264 | | 7z=10z^2 | | (z+5)*(z+8)= | | 8n-(-2)=6/6 | | -69+x=138-8x | | -69+x=138 | | 4k-6=-2k-16-1 | | 4sinx=0 | | 17.95=1.2x+3 | | 8x-54=51+x | | y=1.2(17.95)+3 | | X+3-(x+3)=6 | | (5x+7)(3x-4)= | | 3x-2=5x+11 | | S(t)=160+48t-16t^2 | | 840+17=760+22 | | 6y-6=7y-2y | | y=0.2(10)+2.5 | | 7-3lnx=5 | | 740189302=5 | | -66+9x=4x+84 | | X^2-10=6x | | y=-0.8(55)+72 | | (w+2)*(w-8)= | | 2x^3-3x-5x^2=0 | | n=30/4/7 | | 6x+5=3x+25 |